2005
DOI: 10.1038/nm1291
|View full text |Cite
|
Sign up to set email alerts
|

PI3Kγ inhibition blocks glomerulonephritis and extends lifespan in a mouse model of systemic lupus

Abstract: Systemic lupus erythematosus (SLE) is a chronic inflammatory disease generated by deregulation of T cell-mediated B-cell activation, which results in glomerulonephritis and renal failure. Disease is treated with immunosuppressants and cytostatic agents that have numerous side effects. Here we examine the use of inhibitors of phosphoinositide 3-kinase (PI3K) gamma, a lipid kinase that regulates inflammation, in the MRL-lpr mouse model of SLE. Treatment reduced glomerulonephritis and prolonged lifespan, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
241
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(258 citation statements)
references
References 11 publications
15
241
0
2
Order By: Relevance
“…Newly identified inhibitors which all compete with ATP for binding to the kinase active site have been useful tools in elucidating the role of p110 isoforms in various pathologies such as growth and metabolic regulation , asthma (Ali et al, 2004), inflammation (Barber et al, 2005), arthritis (Camps et al, 2005) and thrombosis (Jackson et al, 2005). Our data show that isoform-specific inhibitors can block the oncogenicity of class I PI3Ks.…”
Section: Oncogenic Signaling Of Class I Pi3k Isoforms a Denley Et Almentioning
confidence: 77%
“…Newly identified inhibitors which all compete with ATP for binding to the kinase active site have been useful tools in elucidating the role of p110 isoforms in various pathologies such as growth and metabolic regulation , asthma (Ali et al, 2004), inflammation (Barber et al, 2005), arthritis (Camps et al, 2005) and thrombosis (Jackson et al, 2005). Our data show that isoform-specific inhibitors can block the oncogenicity of class I PI3Ks.…”
Section: Oncogenic Signaling Of Class I Pi3k Isoforms a Denley Et Almentioning
confidence: 77%
“…In addition, our results suggest that blocking the PI(3)Kg by AS 605402 can effectively interfere with loss of endothelial barrier function provoked by vGPCR, therefore placing PI(3)Kg activity as a multi-functional molecular target for the treatment of patients with KS. Of note, suppression of PI (3)Kg action has been successfully tested in animal models for several pro-angiogenic and pro-inflammatory diseases, such as retinal hyper-permeability, glomerulonephritis, joint inflammation and rheumatoid arthritis (Barber et al, 2005;Camps et al, 2005;Gavard et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, some reports suggested that class IA PI3K might also be activated by GPCRs and may play a role in chemokine receptor-mediated IL-1␤ induction in primary human monocytes (35)(36)(37)(38). To define the role of specific PI3K isoforms on gp120-stimulated IL-1␤ release, we used the class IA PI3K-specific inhibitor PI-103 (39) and the class IB PI3K specific inhibitor AS605240 (40,41). As shown in Fig.…”
Section: Activation Of Pi3k Is Necessary For Gp120-triggered Il-1␤ Inmentioning
confidence: 99%